2022
DOI: 10.1002/acr.24866
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cardiovascular Disease and Mortality Versus Risk of New‐Onset Diabetes Mellitus With Statin Use in Patients With Rheumatoid Arthritis

Abstract: Objective. To assess the effect of statin use on the risk of cardiovascular disease (CVD), all-cause mortality, and type 2 diabetes mellitus (DM) in patients with rheumatoid arthritis (RA).Methods. We identified a cohort of patients with RA between 1989 and 2018, within the UK Clinical Practice Research Datalink. We employed a prevalent new-user cohort design by which patients initiating statins were each matched to 2 concurrent nonusers by the time-conditional propensity score (TCPS). Patients were followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Then, an ‘ever since treatment start’ approach was used in which any drug discontinuation disregarded was also used with a maximum of (3) 1-year, (4) 2-year and (5) 5-year follow-up (online supplemental figure 1). The ‘on-drug’ approach is conceptually similar to an ‘as-treated’ approach used in randomised controlled trials (RCT), while the ‘ever since treatment start’ is similar to an intention-to-treat approach 32. This latter approach could result in one event being attributed to more than one medication.…”
Section: Methodsmentioning
confidence: 99%
“…Then, an ‘ever since treatment start’ approach was used in which any drug discontinuation disregarded was also used with a maximum of (3) 1-year, (4) 2-year and (5) 5-year follow-up (online supplemental figure 1). The ‘on-drug’ approach is conceptually similar to an ‘as-treated’ approach used in randomised controlled trials (RCT), while the ‘ever since treatment start’ is similar to an intention-to-treat approach 32. This latter approach could result in one event being attributed to more than one medication.…”
Section: Methodsmentioning
confidence: 99%
“…The final step of the PNU process involves creation of a matched cohort based on matching study drug users to comparator drug users based on the TCPSs. Whilst the majority of studies (60%) implemented one‐to‐one (1:1) matching without replacement (which is consistent with the Suissa et al proposal), studies also matched one‐to many (1: m ; m ranging from 2 to 4) 6,7,21,23,24 . Of the studies matching 1: m , it was not always clear how this was achieved, for example, if investigators attempted to obtain matches iteratively or all at once.…”
Section: Resultsmentioning
confidence: 62%
“…The PNU design has been implemented in both electronic health records systems (e.g., in the United Kingdom and Hong Kong) [6][7][8] and administrative databases (e.g., in Taiwan, the United States and Canada). 4,[9][10][11][12] Most studies (73%) included use of an electronic health record (EHR) or detailed longitudinal registry database, rather than administrative insurance claims database.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%
“…A total of 665 citations were identified, and 210 potentially eligible articles were retrieved in full text. Overall, 54 studies were included in the review ( Figure 1 ) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Risk of bias assessment using NOS showed that the studies have low risk of bias.…”
Section: Resultsmentioning
confidence: 99%